Bonus Taxes and International Competition for Bank Managers - Daniel Gietl; Andreas Haufler (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
We analyze the competition in bonus taxation when banks compensate their managers by means of fixed and incentive pay and bankers are internationally mobile. Banks choose bonus payments that induce excessive managerial risk-taking to maximize their private benefits of existing government bailout guarantees. In this setting the international competition in bonus taxes may feature a ŕace to the bottomór a ŕace to the top\', depending on whether bankers are a source of net positive tax revenue or inflict net fiscal losses on taxpayers as a result of incentive pay. A ŕace to the topb́ecomes more likely when governmentsímpose only lax capital requirements on banks, whereas a ŕace to the bottomís more likely when bank losses are partly collectivized in a banking union.
Keywords: H20; H87; G28; 330; bonus taxes; international tax competition; migration